Creativity inhibitors in higher education: a student perspective - Matos, Hélio Trindade de; Ramos, Heidy Rodriguez; Rodrigues, Jaime Blanco (Revista de Administração da UFSM, 2019)
This article presents the inhibitory factors perceived by Business Administration students to the promotion of adequate conditions for creativity expression and development in professional training. It investigates the factors inhibiting the promotion of creativity in Higher Education, pointed out individually in the literature, but also investigates them collectively in three groups: board of the higher education unit, pedagogical coordination and teaching staff. The research was carried out in Higher Education Institutions (HEI), both private and public, with the participation of 262 students. The results indicated that the main factors inhibiting creativity promotion are those related to the board and the teaching staff of HEI. Individually the three main inhibitory factors pointed out by the students were: scarcity of material resources, high number of students in the classroom and presence of undisciplined students that disrupt teaching work. It should be noted that the perception regarding inhibitory factors did not vary among students from public and private institutions.